Theory Contribution of Thorndike's Theory in Learning Basic Braille Alphabet for Students with Visual Impairments in SLB - Misbahul Arifin; Sunardi Sunardi (Journal of Disability, 2023)
The development of paradigms in education has implications for practices that take place in almost all lines of education, both formal education institutions and informal education institutions, including in special schools. One of the lessons conducted in SLB is the teaching of Braille letters starting from basic Braille teaching, to expert level Braille.In its teaching, especially the teaching of basic Braille writing, tends to use repetition in its teaching. Repetition is intended to reinforce students with visual impairments in mastering the codes in Braille. In this article, the contribution of Thorndike's theory in teaching Braille alphabet letters to students with visual impairments will be explained. This research uses a qualitative descriptive method, with interview data collection techniques and analyzed descriptively.The results of the research that has been conducted show that Thorndike's Theory has a great contribution in teaching basic Braille letters for students with visual impairments because in teaching it uses repetition in writing the dot codes of the Braille alphabet letters. The repetition aims to make students with visual impairments master the dot codes in the Braille alphabet.